Visualising risk in generating capacity adequacy studies using clustering and prototypes - Tindemans,SH; Strbac,G (IEEE, 2015)
Generating capacity adequacy studies play a significantrole in long term capacity planning. Risks of capacitydeficits are usually reported in the form of one or more averagequantities, which cannot fully convey the nature of the risksbeing faced. Chronological Monte Carlo simulations may be usedto construct comprehensive multi-dimensional risk profiles, butsuch profiles tend to be difficult to interpret. This paper proposesthe use of a clustering method to partition the risk profile intoclusters of similar outcomes with associated probabilities. Theresults are presented in accessible tabular form, and prototypicalscenarios can be analysed in detail to provide further insight.